Antidepressive-Like Effect of Aegle marmelos Leaf Extract in Chronic Unpredictable Mild Stress-Induced Depression-Like Behaviour in Rats. (24th December 2022) - Sharma, Ashwani; Singh, Talever; Pathak, Devender; Virmani, Tarun; Kumar, Girish; Alhalmi, Abdulsalam
Abstract : Background . Depression is a psychiatric disorder leading to anhedonia and lack of interest and motivation. Depressive symptoms are triggered by stressful life events, and patients with major depression are at significantly increased risk of attempting suicide. The crucial concern in depression treatment with antidepressant medications is that few weeks are required to show the therapeutic effect along with moderate side effects. The use of herbal medications is a new strategy for the treatment of depression which is often based on medicinal plants. Aegle marmelos (L.) Corr. (family: Rutaceae) is reported to have several actions on the central nervous system producing beneficial effects in anxiety, Alzheimer's disease, Parkinson's disease, epilepsy, and convulsion. Thus, the current investigation designed to assess the antidepressant activity of the standardized hydroethanolic extract of Aegle marmelos (EAM) leaves in male rats exposed to the chronic unpredictable mild stress (CUMS) paradigm. Methods . Rats were divided in 5 groups. The control group was not subjected to experimental CUMS paradigm, while 4 other groups were subjected to CUMS paradigm to induce depression-like behaviour from day 1 to day 28. Following the CUMS paradigm, 4 groups were divided as CUMS disease control, CUMS+EAM (150 mg/kg, p.o.), CUMS+EAM (300 mg/kg, p.o.), and CUMS+imipramine (15 mg/kg, p.o.), and treatment was given for seven consecutive days to the respective groups (day 29 to day 35). Behavioural parameters such as open field test, forced swim test, sucrose feeding test, and tail suspension test on day 1, day 28, and day 35 were measured, and biochemical parameters such as plasma corticosterone level, serotonergic system (5-HT, 5-HIAA, and 5-HT/5-HIAA), mitochondrial function, and proinflammatory mediators (TNF- α, IL-1 β, and IL-6) were estimated in hippocampus (HIP) and prefrontal cortex (PFC) regions of the brain on day 35, after the behavioural observations. On the other hand, phytochemical profile of Aegle marmelos was done. Results . On day 35, EAM (300 mg/kg) significantly reduced the immobility time during the tail suspension test from 208.66 ± 4.72 s to 108.83 ± 4.81 s and forced swim test from 200.16 ± 4.12 s to 148.5 ± 4.58 s . It also enhanced the behavioural parameters in the open field test such as ambulation from 26.5 ± 2.14 to 56.5 ± 1.80, rearing from 8.33 ± 0.71 to 19 ± 0.57, time spent in centre from 9.16 ± 0.9 to 17.16 ± 0.79 s, total distance travelled from 2.36 ± 0.12 to 4.68 ± 0.10 m, and anhedonia in the sucrose feeding test from 109.33 ± 1.08 to 135.83 ± 3.91 mL . The stimulation of the HPA axis resulting elevated corticosterone level caused by CUMS was reduced by EAM (300 mg/kg) from 80.12 ± 2.020 to 48.25 ± 2.407 μ g / dL . Furthermore, EAM (300 mg/kg) increase CUMS-induced changes in serotonin (5-HT) level in HIP and PFC from 3.132 ± 0.09586 to 4.518 ± 0.1812 and 4.308 ± 0.1593 to 5.262 ± 0.1014 ng / mg protein, respectively. EAM (300 mg/kg) significantly attenuated the CUMS-induced changes in proinflammatory cytokine production and mitochondrial function in HIP and PFC. One group used to determine the acute toxicity as per OECD-23 standard protocol which resulted that 300 mg/kg EAM has no significant acute toxicity. Total phenolic content and total flavonoid content of standardized hydroalcoholic extract of AM was found 95.024 ± 2.431 and 36.820 ± 3.41, respectively, and additional identification tests showed the presence of alkaloids, tannins, saponins, cardiac glycosides, flavonoids, and terpenoids. Conclusion . On the basis of findings, EAM can be inferred as a potential antidepressant-like effect of this plan in preclinical research.